Acute Neuromuscular Fatigue of a Random Vs Constant Session of Repeated Standing Long Jumps. - Dhote, Sylvain; Gimenez, Philippe; Grosprêtre, Sidney (Journal of Sports Science & Medicine, 2024)
There is little evidence of the acute effect of random practice, performed by solely varying the intensity but not the task itself, as compared to block practice, i.e. when one task is repeated in a constant manner. This study aimed to examine the acute neuromuscular effects of physical exercise consisting of repeated jumps of randomized length. Fifteen healthy young participants completed 2 separate sessions of 90 minutes. They did 20 minutes of fatiguing exercise, consisting of 100 repeated standing long jumps (SLJ), in two different manners: one session with targeted jump length kept constant (CO), and one with targeted jump length being varied and unpredictable (RA). Pre- and post-tests were conducted before and immediately after, including measurements of Countermovement Jump (CMJ), SLJ, leg extension maximal voluntary isometric contractions (MViC), EMG activities of leg muscles and patellar tendon reflex amplitude (T-reflex: strike force and evoked force). Results showed that performances decreased after the repeated SLJs, independently of the condition (MViC decreased from 448 ± 118 N to 399 ± 122 N; CMJ decreased from 36.7 ± 7.2 cm to 34.6 ± 6.6 cm). EMG during MViC decreased by 21 ± 28 % from pre- to post-intervention. T-reflex decreased after both conditions ([Force/Strike] ratio decreased by 38 ± 69 % from pre to post). Subjective measures showed a greater sense of personal performance and enjoyment after the RA session. Results suggest that a randomly organized intensity of effort led to a similar decrease in physical performance compared to constant intensity when the session loads were matched. It also led to similar fatigue of the neuromuscular system as shown by T-reflexes and EMG measures. Nonetheless, random practice presents the benefit of being markedly more appreciated by participants.